Spatial Nano-Morphology of the Prolamellar Body in Etiolated Arabidopsis thaliana Plants With Disturbed Pigment and Polyprenol Composition - Bykowski, Michał; Mazur, Radosław; Buszewicz, Daniel; Szach, Joanna; Mostowska, Agnieszka; Kowalewska, Łucja (Frontiers in Cell and Developmental Biology, 2020)
The prolamellar body (PLB) is a periodic bicontinuous membrane structure based on tubular tetrahedral units. PLBs are present in plant etioplasts and, upon illumination, directly transform into the lamellar thylakoid networks within chloroplasts. Efficient tubular-lamellar rearrangement and later formation of the photosynthetically active thylakoid membranes are crucial steps in the development of plant autotrophy. PLB membranes are mainly composed of galactolipids, carotenoids, and protochlorophyllide (Pchlide), the chlorophyll precursor, bound in a complex with NADPH and Pchlide oxidoreductase. Although the PLB structure has been studied for over 50 years, the direct role of particular membrane components in the formation of the PLB paracrystalline network remains elusive. Moreover, despite the numerous literature data regarding the PLB geometry, their reliable comparative analysis is complicated due to variable experimental conditions. Therefore, we performed comprehensive ultrastructural and low-temperature fluorescence analysis of wild type Arabidopsis thaliana (Arabidopsis) seedlings grown in different conditions typical for studies on etiolated seedlings. We established that the addition of sucrose to the growing media significantly affected the size and compactness of the PLB. The etiolation period was also an important factor influencing the PLB structural parameters and the ratio of free to complex-bound Pchlide. Thus, a reliable PLB structural and spectral analysis requires particular attention to the applied experimental conditions. We investigated the influence of the pigment and polyprenol components of the etioplast membranes on the formation of the PLB spatial structure. The PLB 3D structure in several Arabidopsis mutants (ccr1-1, lut5-1, szl1-1npq1-2, aba1-6, pif1, cpt7) with disturbed levels of particular pigments and polyprenols using electron tomography technique was studied. We found that the PLB nano-morphology was mainly affected in the pif1 and aba1-6 mutants. An increased level of Pchlide (pif1) resulted in the substantial shift of the structural balance between outer and inner PLB water channels and overall PLB compactness compared to wild type plants. The decrease in the relative content of β-branch xanthophylls in aba1-6 plants was manifested by local disturbances in the paracrystalline structure of the PLB network. Therefore, proper levels of particular etioplast pigments are essential for the formation of stable and regular PLB structure.